Model Pembelajaran Blended Learning dengan Pendekatan Knowledge Management System untuk Sekolah Dasar XYZ - Theresia Evy Yulianty Nadeak; Dewi Mustari; Retna Ningsih (Jurnal Ilmiah Wahana Pendidikan, 2021)
Elementary school is the most basic level of formal education in Indonesia. Elementary school is taken within 6 years, starting from grade 1 to grade 6 (Wikipedia, 2021). Therefore, elementary school education is very important because it is a benchmark for children's success in receiving basic education. So basic education must have quality resources. Good teaching materials supported by qualified teaching staff. This pandemic period, of course, shifts from face-to-face learning to online learning. In implementing the online learning model with the blended learning method, Google Meet is used as the learning medium. In addition, in this study using a Knowledge Management System (KMS) can help problems regarding migration from face-to-face learning to learning with blended learning models. The problems that arise from learning the blended learning model are of course the readiness of teachers, technology and equipment needed to support implementation. This research method uses a descriptive content analysis study. The result of this research is a blended learning-based learning model with knowledge management system modeling for teaching materials.